ESTIMATION OF EFFICIENCY OF MACHINERY FOR PRE-SOWING TREATMENT OF RADISH SEEDS FOR SEED PRODUCTION - S. M. Sirota; A. N. Kalinin; T. E. Shevchenko (Овощи России, 2016)
The results of pre-sowing treatment of radish seeds aimed at increasing of seed production, yield and its productivity in protected area are presented. The density fractionation of radish seeds by gravity separator is recommended for improvement of planting material quality and increasing of utilization efficiency of frame area.